Forty years of the Ellis–Baldwin test - Secrest, N; von Hausegger, S; Rameez, M; Mohayaee, R; Sarkar, S (Springer Nature, 2025)
Modern cosmology is built on the assumption that the Universe is homogeneous and isotropic on large scales — but this is challenged by results of the Ellis–Baldwin test that show an unexplained anomaly in the distribution of distant galaxies and quasars.